Stochastic diffusion characterises early colony formation in Mediterranean coral Corallium rubrum. (21st November 2022) - Kahramanoğulları, Ozan; Giordano, Bruna; Perrin, Jonathan; Vielzeuf, Daniel; Bramanti, Lorenzo
Abstract: The colony formation in Mediterranean coral Corallium rubrum is initiated by a larva that metamorphoses into the first polyp of the emerging colony approximately two weeks after settlement. The primary polyp then sets up a slow process that eventually, at least after a few years, gives rise to a tree-like rigid colony structure on which other polyps flourish. For a mature colony, this axial skeleton provides support for new polyps. However, the first emergence of the characteristic axial skeleton can take two years or more from the larva stage. The early colony morphology, instead, is shaped exclusively by the polyps' abundant deposition of sclerites, a magnesian calcite biomineral that has a different granularity from the distinctive red-coloured skeleton. With the appearance of the first polyp, a growing sclerite heap in a mesoglea layer provides a base for the emerging colony. In this paper, to elucidate the mechanical processes of early skeleton development in C. rubrum colonies, we present a computational model whereby the mesoglea layer provides a diffusion medium for the sclerites that the polyps deposit. We show that our stochastic model with three parameters captures the dynamic variability observed in measurements on living colonies. Our simulation results provide evidence for a diffusion process whereby the interplay between polyp budding and sclerite deposition are the main determinants of structure in early colony formation. Our model demonstrates that the frequency of budding events in an early colony can be described as a function of the available mesoglea surface whereas the number of polyps on the colony plays a secondary role in determining this frequency. We show that these model predictions are confirmed by direct observations on the colonies in our sample. Moreover, our results indicate that diffusion is a prevalent mechanism of colony development also at later stages of a colony's life span. Highlights: A stochastic model of early colony development in Corallium rubrum is proposed. Samples of 1- and 2-year-old colonies are used for model fitting and verification. Simulations based on diffusion quantitatively capture early colony development. The frequency of polyp budding is only indirectly affected by the number of polyps. The budding frequency remains unaffected with the availability of sufficient surface.